Peramalan Supply Bahan Baku Menggunakan Metode Regresi Linier dan Exponential Smoothing - Salsavira, Nardha; Yuliawati, Evi (Universitas Nusantara PGRI Kediri, 2023)
Production process that happened in manufacturing industry will never be seperated from production planning and scheduling. This was closely related to sustainablity of company. Uncertainty of production targets or the amount of supply that must be obtained often becomes an issues in some companies. It can be solved with production planning and control as the first step that can be taken to make production process balanced with market. This research aims to facilitate production management in scheduling operations by forecasting erratic supply. Forecasting can be done with linear regression and exponential smoothing use POM QM as software assistance. Based on calculation result, exponential smoothing was an optimal method used for forecasting than linear regression. It can be concluded from the lowest result of the error rate test. Error rate test was done with MAD (Mean Absolute Deviation), MSE (Mean Square Error) and MAPE (Mean Absolute Percentage Error)